The Riyadh Urban Growth Boundary: An Analysis of the Factors Affecting its Efficiency on Restraining Sprawl (International Journal of Built Environment and Sustainability, 2021)
Recently, research on sprawl was increasing due to its impacts on the economy, society, and environment. Several studies have focused on the application of containment strategies to curb urban sprawl. Urban growth boundaries (UGBs) were among the containment policies adopted to tackle the issue of sprawling cities. This paper set out to undertake an analysis of the factors influencing the performance of the UGB of Riyadh City. A qualitative data analysis using NVivo12 software was adopted. To collect the required data of UGB, semi-structured interviews were conducted with nine experts involved in urban management, Riyadh city development, and other planning agencies. If the application of UGB policy in the western countries has managed to restrain more or less city sprawl, its replication to the case of Riyadh seems to have had some adverse impacts. That is, instead of controlling urban sprawl, it has stimulated it. The reasons may lie in the deficiency of monitoring and evaluation of urban studies, free provision of infrastructure, and lack of coordination between different city planning agencies. Understanding the factors affecting the UGB efficiency​will assist policymakers and urban planners in reducing the spread of scattered and leapfrog residential development, lowering the cost of service supply and promoting infill development
Keywords: Urban growth boundary; Growth Management; Urban Sprawl; Urban containment strategies; Saudi Arabia